Airborne Benzene Concentrations Increase Trans, Trans-Muconic Acid (tt-MA) Levels and Liver Function in Workers in The Manufacturing Industry - Kahar; Hasan, Nia Yuniarti; Prijanto, Teguh Budi; Kamaludin, Ade (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
The use of benzene as a solvent in the manufacturing industry can be dangerous because it is volatile, toxic, and carcinogenic. Exposure to benzene occurs through inhalation of the chemical in the air, which can enter the human body through the respiratory system. The levels of trans, trans-Muconic Acid (tt-MA), which is used to metabolize benzene, can be affected by the amount of exposure to the chemical. This study aims to determine the differences in exposure to benzene in the air by measuring the tt-MA indicators and liver function of workers in the manufacturing industry. This research uses an observational and cross-sectional approach, with a population of 158 employees from both administration and production units. The sample size for the study is 16 respondents, selected using the consecutive sampling technique. The research instrument uses a questionnaire and examines urine samples using the in-house method. Blood samples are examined using IFCC 37 C. The data is processed using the independent-sample t-test and Pearson correlation. The results show that the level of benzene in the air is below the threshold of 0.5 ppm. However, there is a significant difference in the results of tt-MA and SGOT (p less than 0.05), while the levels of SGPT (p greater than 0.05) show no significant differences. In conclusion, there are differences in the tt-MA and SGOT exposure levels between workers in the production and toxicity units, while SGPT does not show significant differences. It is recommended that the industry maximizes the use of local exhaust ventilation and prohibits smoking.